Overcoming Barriers to Persistence for First-Generation Adult Community College Students - Jennifer A. Boulanger (Adult Education Research Conference, 2009)
The study sought to understand first-generation adult community college students’ persistence strategies, their origins and development. The main research question, “What strategies do first-generation adult community college students employ to enable them to stay in college?” is addressed by exploring participant responses related to four sub-questions: (1) How are the strategies employed by first-generation adult community college students shaped? (2) What individual strategies do first-generation adult community college students employ to enable them to stay in college? (3) How do institutional characteristics interact with individual characteristics to influence persistence? (4) To what extent do practitioners’ perspectives corroborate student reports of effective strategies? A qualitative design that incorporated a selfnominating survey, critical incident, interview, and engagement with a focus group provided a wealth of data that was coded and analyzed.